2015
DOI: 10.1007/s10008-015-2980-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrochemical sensor based on Fe2O3 nanoparticles/N-doped graphene for electrocatalytic oxidation of L-cysteine

Abstract: A novel electrochemical sensor based on Fe 2 O 3 nanoparticles supported on N-doped graphene (Fe 2 O 3 NPs/N-GR) has been fabricated for electrocatalytic oxidation and detection of L-cysteine. The Fe 2 O 3 NPs/N-GR was characterized by scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy (XPS), and electrochemical methods. The electrochemical behavior of L-cysteine at Fe 2 O 3 NPs/N-GR was investigated by voltammetry. The Fe 2 O 3 NPs/N-GR showed a very efficient electrocatalytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…An irreversible electrochemical CV peak located at about +1.05 V was observed at the Fe 2 O 3 nanoparticles supported on N-doped graphene (Fe 2 O 3 NPs/N-GR) GCE in the presence of 0.5 mM L-cysteine and 0.1 PBS with the scan rate of 50 mV·s -1 . 18 A pair of semi-reversible redox peaks at -0.07 V and -0.52 V was observed at the Zn bismuthate nanorods modified GCE in 2 mM L-cysteine and 0.1 M KCl solution. 5 Two pairs of CV peaks of L-cysteine at the polyaniline/ CuGeO 3 nanowires modified GCE were located at +0.24 V (cvp1), +0.07 V (cvp2) and +0.05 V (cvp1′), -0.47 V (cvp2′) in 2 mM L-cysteine.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…An irreversible electrochemical CV peak located at about +1.05 V was observed at the Fe 2 O 3 nanoparticles supported on N-doped graphene (Fe 2 O 3 NPs/N-GR) GCE in the presence of 0.5 mM L-cysteine and 0.1 PBS with the scan rate of 50 mV·s -1 . 18 A pair of semi-reversible redox peaks at -0.07 V and -0.52 V was observed at the Zn bismuthate nanorods modified GCE in 2 mM L-cysteine and 0.1 M KCl solution. 5 Two pairs of CV peaks of L-cysteine at the polyaniline/ CuGeO 3 nanowires modified GCE were located at +0.24 V (cvp1), +0.07 V (cvp2) and +0.05 V (cvp1′), -0.47 V (cvp2′) in 2 mM L-cysteine.…”
Section: Resultsmentioning
confidence: 96%
“…Various methods have been used for the determination of L-cysteine, such as photoelectrochemical detection, 14 spectrometric method, 15,16 chromatographic separation method 17 and electrochemical method. 18 Among these methods, electrochemical method using GCE modified with nanoscale materials has been widely reported to improve the selectivity and sensitivity for the detection of organic acids. However, the electrochemical determination of L-cysteine on the conventional electrodes requires large overpotential which significantly reduces the selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 93 ] synthesized a ternary nanocomposite of platinum, magnetite and reduced graphene oxide, referred to as Pt-Fe 3 O 4 /rGO, by a solvothermal method for sensitive determination of cysteine in 0.1 M NaOH. Using this modification allowed them to determined cysteine in the concentration range of 0.1–1 M with a detection limit of 10 µM which was one order of magnitude lower than previous report [ 67 ]. Taking advantage of β-cyclodextrin, β-CD, in combination with Fe 3 O 4 modified graphene oxide (MGO) which had been prepared by a simple coprecipitation method, let Wang et al [ 131 ] to determine tryptophan in the linear range of 5.0 × 10 −7 to 7.5 × 10 −4 M with a detection limit of 3.1 × 10 −7 M. Simple scheme of fabrication of this modified electrode has been shown in Figure 15 .…”
Section: Applicationmentioning
confidence: 85%
“…Cysteine [ 67 , 93 ], tryptophan [ 131 ], phenylalanine [ 132 ], tyrosine and aspartic acid [ 133 ] are among the most important amino acids which have been successfully quantified using iron based graphene composites as a modifier. A composite of Fe 2 O 3 nanoparticles supported on N-doped graphene, Fe 2 O 3 NPs/N–GR (Nitrogen doped Graphene), was successfully prepared through a hydrothermal route starting from FeSO 4 ·7H 2 O and graphene oxide as reactants followed by dropwise addition of ammonium hydroxide 30% and transferring this mixture to autoclave where it was held for 12 h at 180 °C to obtain abovementioned composite [ 67 ]. SEM analysis demonstrated that individual Fe 2 O 3 NPs with a diameter of about 45 nm have been well spread out on the graphene sheets.…”
Section: Applicationmentioning
confidence: 99%
“…Nowadays considerable research has been shifted to metal oxide modified electrodes for the determination of CysH (e. g. iron oxide, zinc oxide, manganese oxide, etc.) , because metal oxide based electrochemical sensors possess unparalleled merits such as cost effectiveness, good selectivity, high sensitivity and stability.…”
Section: Introductionmentioning
confidence: 99%